The Microstructure of Isichazamazwi SesiNdebele - Maphosa, Mandlenkosi; Nkomo, Dion (Buro van die WAT, 2021)
This article analyses the microstructure of Isichazamazwi SesiNdebele. The analysis takes place on two levels: the level of availability of information and the level of accessibility of the available information to dictionary users. Data derived from two outreach exercises carried out to ascertain users' perspectives on the dictionary and their competence in using the dictionary is also scrutinised while the notion of user-friendliness and the general principles of dictionary-making form the framework within which the analysis is done.